2010
DOI: 10.4102/sajip.v36i1.850
|View full text |Cite
|
Sign up to set email alerts
|

Turnover of nursing employees in a Gauteng hospital group

Abstract: <strong>Orientation:</strong> The South African nursing profession is in a crisis as professional nurses leave the country in search of lucrative work overseas.<p><strong>Research purpose:</strong> The purpose of this study was to investigate individual determinants of voluntary turnover to identify a risk-group profile.</p><p><strong>Motivation for the study:</strong> Nursing employers should have a clearer understanding of the dynamics around nurses&r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…The study highlighted the moderating role of some biographical and demographical variables in the voluntary employee turnover process. The associated impact of voluntary employee turnover on profit margins is well documented in relevant literature (Bluedorn, 1982;Greyling & Stanz, 2010;Mobley, 1982).…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…The study highlighted the moderating role of some biographical and demographical variables in the voluntary employee turnover process. The associated impact of voluntary employee turnover on profit margins is well documented in relevant literature (Bluedorn, 1982;Greyling & Stanz, 2010;Mobley, 1982).…”
Section: Resultsmentioning
confidence: 91%
“…Studies reporting results on reasons why employees choose to leave or stay with a particular organisation (Bothma & Roodt, 2012;Du Plooy & Roodt, 2010;Greyling & Stanz, 2010;Griffeth, Hom & Gaertner, 2000;KotzĂ© & Roodt, 2005;Mendes & Stander, 2011) are gaining importance and most of them focus on a set of negative consequences associated with employee turnover (Bluedorn, 1982;Greyling & Stanz, 2010;Mobley, 1982;Roodt & Bothma, 1997). Corporate sustainability issues are gaining momentum and an example of this is the behaviour of the modern and informed investor who no longer assesses the quality of the organisation at present, but the organisation's risk management and whether it has established sustainability strategies pertinent to its business (King III Report, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternative employment opportunities therefore influence actual labour turnover behaviour (Agarwal et al, 2007;AkgĂŒn & Lynn, 2002;Allen & Meyer, 1996;Bellou, 2008;Boies & Rothstein, 2002;Brown, 1996;Carmeli & Gefen, 2005;Chen, Chu, Wang & Lin, 2008;Jaros et al, 1993;Lee & Mitchell, 1994;Martin & Roodt, 2008;Mobley, 1982;Senter & Martin, 2007;Wheeler, Gallagher, Brouer & Sablynski, 2007). Bothma (2011) concluded that the turnover phenomenon has significant cost and other negative consequences for any organisation (Bluedorn, 1982;Greyling & Stanz, 2010;Mobley, 1982). Losing employees that are highly skilled may have disruptive implications for organisations, such as impaired organisational functioning, service delivery and administration.…”
Section: Theoretical Models That Explain Turnover Intentionsmentioning
confidence: 99%
“…Bothma & Roodt, 2012;Du Plooy & Roodt, 2010;Greyling & Stanz, 2010;Griffeth, Horn, & Gaertner, 2000;KotzĂ© & Roodt, 2005;Mendes & Stander, 2011). Turnover intentions (intentions to stay or leave the organisation) is an important criterion variable in similar types of studies, but such studies seldom publish any additional validation information on these criterion measures.…”
Section: Introductionmentioning
confidence: 99%